2021
DOI: 10.1039/d1qm00338k
|View full text |Cite
|
Sign up to set email alerts
|

Agar/carbon dot crosslinked polyacrylamide double-network hydrogels with robustness, self-healing, and stimulus-response fluorescence for smart anti-counterfeiting

Abstract: From the perspective of sustainable economic development, advanced fluorescent anti-counterfeiting technology is trying to encrypt information onto polymer materials with toughness, self-healing, and stimulus-responsive properties. Herein, a low cost and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…18 To date, the development of self-healing hydrogels with an adjustable fluorescence still remains a challenge, owing to the water-induced aggregation-caused quenching (ACQ) nature of traditional organic luminogens. 19 Most self-healing hydrogels with reported fluorescence are limited to the inorganic luminogens, 20–23 such as lanthanide complexes, 15,21,23 metal nanoclusters, 16 quantum dots, 22 and so forth. 24,25 Since Tang et al reported the aggregation-induced emission luminogens (AIEgens) in 2001, 26 the unique characteristics of AIEgens have overcome the drawbacks of ACQ, ultimately yielding high levels of fluorescence emission in the aggregated state 27–29 and making modulated fluorescence, with a high fluorescent intensity, possible.…”
Section: Introductionmentioning
confidence: 99%
“…18 To date, the development of self-healing hydrogels with an adjustable fluorescence still remains a challenge, owing to the water-induced aggregation-caused quenching (ACQ) nature of traditional organic luminogens. 19 Most self-healing hydrogels with reported fluorescence are limited to the inorganic luminogens, 20–23 such as lanthanide complexes, 15,21,23 metal nanoclusters, 16 quantum dots, 22 and so forth. 24,25 Since Tang et al reported the aggregation-induced emission luminogens (AIEgens) in 2001, 26 the unique characteristics of AIEgens have overcome the drawbacks of ACQ, ultimately yielding high levels of fluorescence emission in the aggregated state 27–29 and making modulated fluorescence, with a high fluorescent intensity, possible.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Most materials only require one simple stimulus to decrypt the stored data, resulting in a low-level of data security. 24–26…”
Section: Introductionmentioning
confidence: 99%
“…(2) Most materials only require one simple stimulus to decrypt the stored data, resulting in a low-level of data security. [24][25][26] In chemistry, configurational isomers are a group of molecules with identical elemental constitutions and molecular formulas, very similar chemical structures and physiochemical properties, but different configurations. [27][28][29] Using configurational isomers as data storage and encryption media could potentially render many unique advantages, including (1) eliminating the risk associated with data deciphering via sophisticated instrumental analysis (e.g., Fourier-transform infrared spectroscopy, elemental analysis, energy-dispersive X-ray spectroscopy measurement, and others), (2) providing a high-level of data security due to the very similar physiochemical properties of the isomers, and (3) multiple stimuli, rather than one stimulus, would be required to full decrypt the data.…”
Section: Introductionmentioning
confidence: 99%
“…35 As a polysaccharide representative, agarose 36 has been widely used in biotechnology, medical detection, and pharmacological treatment due to its special hydrophilicity, good biocompatibility, macroporous structure, and thermal-reversible gel properties. 37 Agarose has great potential in CL platform construction due to its good biodegradability and strong gelation ability.…”
Section: Introductionmentioning
confidence: 99%